Influence of babassu fiber content on the chemical, physical and mechanical properties of polyhydroxybutyrate/babassu biocomposites - Camila Ferreira Gerardo; Laysa Silva Barboza; Ana Carolina Bastos Rodrigues; Beatriz Cruz Bastos; Pedro Henrique Poubel Mendonça da Silveira; Sergio Neves Monteiro; Shirleny Fontes Santos; Neyda de La Caridad Om Tapanes; Daniele Cruz Bastos (Journal of Materials Research and Technology)
Polyhydroxybutyrate (PHB)/Babassu fiber biocomposites were developed via compression molding and subjected to extensive characterization. ATR-FTIR analysis indicated physical interactions between the components due to their chemical similarities. XRD patterns revealed minor structural disorganization in the PHB/Babassu 85/15 and 80/20 formulations, with a slight decrease in crystallinity. SEM analysis demonstrated weak polymer-matrix adhesion in these samples, which may affect mechanical performance. The incorporation of babassu increased the water contact angle, enhancing hydrophobicity, particularly in the 90/10 and 80/20 formulations. Tensile tests showed that the PHB/Babassu 90/10 composite maintained mechanical properties comparable to pure PHB, while higher babassu content (20 %) led to decreased performance due to poor interfacial adhesion. Impact resistance was slightly improved in the 90/10 formulation, aligning with hardness results. Thermogravimetric analysis indicated that PHB primarily degrades between 250 and 310 °C, while PHB/Babassu composites exhibited an initial weight loss due to moisture release. Babassu had minimal influence on thermal stability; however, a 10 % filler content increased Tonset by approximately 10 °C, whereas higher concentrations showed negligible variation. The PHB/Babassu 90/10 composition stands out for its balance between mechanical strength and environmental sustainability, making it a promising candidate for biodegradable applications, such as packaging and agricultural films. Further studies should explore improved filler dispersion to enhance mechanical properties and broaden potential applications.